Pengaruh Disiplin Belajar, Self-Efficacy, dan Motivasi Belajar Terhadap Hasil Belajar Ekonomi: The Influence of Learning Discipline, Self-Efficacy, and Learning Motivation on Economics Learning Outcomes - Aliyah, Lia Samrotul; Gumilar, Rendra; Srigustini, Astri (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The problem in this research is the low learning outcomes of students in the economics subject. This study aims to analyze the influence of learning discipline, self-efficacy, and learning motivation on student learning outcomes. The research method used is a survey with an associative research design. The population in this study consisted of 165 twelfth-grade students at SMA Negeri 1 Manonjaya who were enrolled in economics. The sampling technique used was saturated sampling. Data were collected using questionnaires and were analyzed using multiple linear regression analysis. The results showed that there is a positive and significant influence of learning discipline on learning outcomes with a significance value of 0.002; there is a positive and significant influence of self-efficacy on learning outcomes with a significance value of 0.022; there is a positive and significant influence of learning motivation on learning outcomes with a significance value of 0.000; and there is a simultaneous positive and significant influence of learning discipline, self-efficacy, and learning motivation on learning outcomes with a significance value of 0.000.